Urolithiasis in Male Boiler Breeders - Moyle , J.R.; Wideman, R.F.; Whipple, S.M.; Yoho, D.E.; Bramwell, R.K. (International Journal of Poultry Science, 2011)
Mortality often is much higher in male than in female broiler breeders (36.2% vs. 11.1%), making it necessary to introduce additional males during the breeding cycle. While it is known that males perform better on low protein diets, they usually are fed the same diet as the hens in order to reduce feed transportation costs and eliminate the chance of the hens receiving the wrong feed. Hen diets are high in Calcium (Ca) which may be detrimental to male performance and may cause kidney damage as the males excrete the excess Ca. In an effort to understand the extent of kidney damage that occurs in male broiler breeders, 136 males that had been on commercial breeder hen diets for 41 or 42 wks were euthanized and their kidneys evaluated. Data collected included body weight, left and right kidney weights and the incidence of macroscopically visible uroliths within the ureters or ureteral branches. The bilateral symmetry of the two kidneys (heavy:light kidney weight ratio) was assessed as an indicator of subclinical kidney damage. The results revealed that only 55.6% of the males had kidneys that were bilaterally symmetrical (within 10% by weight). Left kidneys were significantly heavier than right kidneys (10.07 vs. 9.26 g, respectively) and the left kidney was larger in 76.3% of the birds. Uroliths were found in 7.4% (10/136) of the males. These results indicate that broiler breeder males fed high levels of Ca develop kidney asymmetry and urolithiasis, which can contribute to their high mortality levels.